CANADIAN EDUCATION IN DISTANCE FORMAT - Sitkar , Victor; Sitkar , Stepan (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The essence of one of the best Canadian education systems in the world is considered. Through the prism of the views of our compatriots, the specifics of distance (online) education in educational institutions of the "maple leaf" country have been characterized. Canadians are convinced that schools are mirrors of communities, or they are also called «microcosms of society». They should be rich and safe, places of opportunity where everyone learns together – children, their parents, and teachers.